Bidirectional two-sample Mendelian randomization analysis reveals a causal effect of interleukin-18 levels on postherpetic neuralgia risk - Liang, Xiao; Fan, Yuchao (Frontiers in Immunology, 2023)
Background: Postherpetic neuralgia (PHN) is a debilitating complication of herpes zoster, characterized by persistent neuropathic pain that significantly impairs patients' quality of life. Identifying factors that determine PHN susceptibility is crucial for its management. Interleukin-18 (IL-18), a pro-inflammatory cytokine implicated in chronic pain, may play a critical role in PHN development. Methods: In this study, we conducted bidirectional two-sample Mendelian randomization (MR) analyses to assess genetic relationships and potential causal associations between IL-18 protein levels increasing and PHN risk, utilizing genome-wide association study (GWAS) datasets on these traits. Two IL-18 datasets obtained from the EMBL's European Bioinformatics Institute database which contained 21,758 individuals with 13,102,515 SNPs and Complete GWAS summary data on IL-18 protein levels which contained 3,394 individuals with 5,270,646 SNPs. The PHN dataset obtained from FinnGen biobank had 195,191 individuals with 16,380,406 SNPs. Results: Our findings from two different datasets of IL-18 protein levels suggest a correlation between genetically predicted elevations in IL-18 protein levels and an increased susceptibility to PHN.(IVW, OR and 95% CI: 2.26, 1.07 to 4.78; p = 0.03 and 2.15, 1.10 to 4.19; p =0.03, respectively), potentially indicating a causal effect of IL-18 protein levels increasing on PHN risk. However, we did not detect any causal effect of genetic liability to PHN risk on IL-18 protein levels . Conclusion: These findings suggest new insights into identifying IL-18 protein levels increasing at risk of developing PHN and may aid in the development of novel prevention and treatment approaches for PHN.